Nurses knowledge about multidrug resistant bacteria in a teaching hospital - Maristela Yoshie Yamaji Okagawa Rocha; Jemima Franco dos Santos Lima; Solena Kuzma; Letícia Pontes; Ricardo Pasquini (Universidade Federal do Ceará, 2019)
Objective: to identify the knowledge of nurses of a teaching hospital about multidrug resistant bacteria. Methods: cross-sectional and prospective study with the participation of 109 nurses. Data collection used a questionnaire with open and objective questions. Statistical analysis used the Statistical Package for the Social Sciences software. Results: 67.0% of the participants considered the knowledge acquired in the graduation regarding multi-resistant bacteria insufficient to deal with them, with a predominance of professionals graduated before the year 2005; in the transmission process, younger professionals predominated. Conclusion: knowledge about multidrug-resistant bacteria was higher among younger, more recently graduated professionals, with proactive enough to expand knowledge about the subject and to participate in in-service training. The Hospital Infection Control Service was the main source of knowledge for nurses participating in the study.